CORROSION DEGRADATION OF S235JR AND S355JR STEELS USED IN THE CONSTRUCTION OF SURFACE MINING EQUIPMENT - Florin CIOFU (Fiabilitate şi Durabilitate)
Metal structures exposed to aggressive environmental conditions are often subject to the loss of protective layers and material degradation over time due to corrosion. This leads to a reduction in the cross-sectional area of the components, an increase in surface roughness, the formation of surface irregularities and corrosion cavities, as well as a decline in the overall set of physical and mechanical properties. The aim of this study is to analyze the fatigue behavior of low-alloy steels under corrosive conditions, specifically those used in the construction of mining equipment for various mining operations in Gorj County